2010
DOI: 10.1086/652807
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Phosphorodiamidate Morpholino Oligomers Targeted to an Essential Gene InhibitBurkholderia cepaciaComplex

Abstract: Background: Members of the Burkholderia cepacia complex (Bcc) cause significant morbidity and mortality in patients with chronic granulomatous disease (CGD) and cystic fibrosis (CF). Many Bcc strains are antibiotic resistant requiring the exploration of novel antimicrobial approaches including antisense technologies, such as phosphorodiamidate morpholino oligomers (PMOs). Methods: Peptide-conjugated PMOs (PPMOs) were developed to target the acpP gene, encoding an acyl carrier protein thought to be essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
78
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 32 publications
3
78
1
1
Order By: Relevance
“…This suggests that the efficacy of PPMOs may not be entirely gene specific. Off target or nonspecific effects of PPMOs have also been observed in vitro with E. coli (Wesolowski et al, 2011) and Acinetobacter lwoffii (Geller, unpublished data), and in vivo with Burkholderia multivorans (Greenberg et al, 2010). Some of this nonspecific effect may be due to partial complementarity of scrambled sequence controls to other genes (Wesolowski et al, 2011).…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…This suggests that the efficacy of PPMOs may not be entirely gene specific. Off target or nonspecific effects of PPMOs have also been observed in vitro with E. coli (Wesolowski et al, 2011) and Acinetobacter lwoffii (Geller, unpublished data), and in vivo with Burkholderia multivorans (Greenberg et al, 2010). Some of this nonspecific effect may be due to partial complementarity of scrambled sequence controls to other genes (Wesolowski et al, 2011).…”
mentioning
confidence: 89%
“…Phosphorodiamidate morpholino oligomers (Geller et al, 2003;Greenberg et al, 2010) have been shown to silence expression of bacterial genes. Gene-silencing oligomers decrease expression of reporter genes such as luciferase, activate endogenous genes such as b-galactosidase, and inhibit growth by targeting essential genes .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The delivery of antibacterial PNA molecules can be achieved by designing of bacterial-specific vehicles. Several peptides, such as (KFF)3K, (R-Ahx-R)4-Ahxβala, (R-Ahx)6-βala, YARVRRRGPRGYARVRRRGPRRC, and RFFRFFRFFRXB, are known for delivering antisense PNA or Morpholino oligomers in bacteria [10,15,22,23]. In addition to their structural and/or sequence dissimilarity, these peptides may also differ in their uptake in bacteria.…”
mentioning
confidence: 99%